The Integrity of International Judicial Rulings in Relation to Sovereign States - Boussakra, Boualem (Journal of Legal Studies and Researches, 2017)
The transformations that followed the outbreak of World War I and World War II, together with the establishment of the United Nations as a global organization, constituted a turning point in international relations. They imposed upon States the obligation to settle disputes arising between them by peaceful means, in order to safeguard international peace and security and to preserve the stability of such relations. To this end, several mechanisms were developed, foremost among them the establishment of a permanent international judiciary, represented by the International Court of Justice, which succeeded the Permanent Court of International Justice, as well as the International Criminal Court. However, international adjudication—being of relatively recent origin—continues to face significant challenges and obstacles no less serious than those encountered during its formation. Chief among these are the constraints imposed by State sovereignty. It has become evident that sovereignty, in its contemporary form, is effectively monopolized by certain States to the detriment of others. This has weakened the authority and effectiveness of international adjudication by rendering it largely consensual in nature and by depriving judicial decisions of enforceable effect in service of sovereign interests. This raises the question of how to explain the absence of accountability for perpetrators of war crimes in Afghanistan and Iraq, and the subsequent criminal scandals attributed to the United States.